Penanaman Karakter Rasa Cinta Tanah Air Pada Anak Usia Dini Dengan Mengenalkan Lagu-Lagu Nusantara Di Tk Amarta Tani - Venna Adeliana; Sulistianah Sulistianah; Qomario Qomario (Universitas Dehasen Bengkulu, 2023)
This research aims to describe the cultivation of the character of love for the country and examine how teachers stimulate young children in introducing and instilling a sense of love for the country at the AMARTA TANI BANDAR LAMPUNG Kindergarten.This research is a research using qualitative methods. Sources of research data obtained from primary data and secondary data. Researchers obtained primary data from interviews with class B2 teachers at Amarta Tani Kindergarten as well as observations of the cultivation of a sense of love for the country. Secondary data was obtained from documentation, in the form of photos of children reflecting their love for their country at Amarta Tani Kindergarten. The data obtained is then collected, reduced, described, tested for the validity of the data and concluded.The results of the research show that a sense of love for the country is instilled in the Amarta Tani Kindergarten in Bandar Lampung. The planting carried out by educators has been very optimal in instilling a sense of love for the country in young children. The feeling of love for the country in the school environment is often instilled through activities in the school environment such as celebrating national holidays, flag ceremonies, singing national songs, getting to know heroes and introducing various diversity and culture in Indonesia. Every child needs to receive regular instillation as early as possible and continuously at every opportunity so that the feeling of love for the country will be embedded in the child from an early age.